Brief mindfulness training increased glutamate metabolism in the anterior cingulate cortex. Issue 16 (4th November 2020) - Tang, Yi-Yuan; Askari, Pegah; Choi, Changho
Abstract : Mindfulness meditation has become a promising intervention for promoting health and well-being. Neuroimaging studies have shown its beneficial effects on brain functional activity, connectivity, and structures following months to years of practice. A series of randomized controlled trials indicated that one form of mindfulness meditation, the integrative body-mind training (IBMT) induces brain functional and structural changes in brain regions related to self-control networks such as the anterior cingulate cortex (ACC) after 2–10 h of practice. However, whether IBMT could change brain metabolism in the ACC remains unexplored. Utilizing a noninvasive 3T proton magnetic resonance spectroscopy, our results showed a significant increase in glutamate metabolism in the rostral ACC following 10 h of IBMT, suggesting that brief training not only increases ACC activity and structure, but also induces neurochemical changes in regions of the self-control networks. To our knowledge, this is the first study demonstrating the positive effects on brain metabolism in the ACC following brief intervention, suggesting a potential mechanism and implications of mindfulness meditation in ameliorating disorders such as addiction, depression and schizophrenia, which often involve the dysfunction of self-control networks and glutamatergic system (i.e. lower glutamate metabolism).